THE INFLUENCE OF CHRONIC INFLAMMATORY PROCESSES ON OVARIAN FUNCTION (International journal of medical sciences, 2026)
This article analyzes the effect of chronic inflammatory processes on ovarian function. Chronic inflammation is a long-term pathological condition in the female reproductive system, leading to the development of morphological and functional changes in ovarian tissues. During the study, microcirculation disorders, stromal fibrosis, slowing down the maturation of the follicular apparatus, and disruption of the steroidogenesis process were identified against the background of inflammatory processes. These changes are manifested by menstrual cycle instability, ovulation disorders, and decreased ovarian reserve. The article substantiates the need to preserve ovarian function and ensure reproductive health in women through early detection and complex treatment of chronic inflammatory processes.